Cross-linguistic influence in the writing of an italian learner of English as a foreign language: an exploratory study - Chapetón, Claudia Marcela (Colombian Applied Linguistics Journal, 2008)
This paper is based on the analysis of the nature of the first language influence on the written production of an Italian learner of English as a foreign language. The goal of the present exploratory study is to examine how cross-linguistic influence manifests itself at the level of syntax and lexis. Findings suggest that forms and meanings in the L2 are expressed and shaped by the learner’s knowledge and use of the foreign language as well as by the influence of the mother tongue.